1993
DOI: 10.1093/ajcn/58.5.666
|View full text |Cite
|
Sign up to set email alerts
|

Comparative efficacy of n−3 and n−6 polyunsaturated fatty acids in modulating ventricular fibrillation threshold in marmoset monkeys

Abstract: Programmed electrical stimulation in anesthetized marmoset monkeys was used to examine relative antiarrhythmic efficacies of dietary n-3 and n-6 polyunsaturated fatty acids (PUFAs) from fish and plant oils. Diets contained 31% of energy (en%) as fat, comprising 15 en% saturated fat and 7 en% PUFAs, obtained by blending sheep fat with sunflower seed (SF/SSO) or fish oil (SF/FO) and a base diet. After 16-wk feeding, ventricular fibrillation (VF) was inducible in 6 of 10 animals on each diet under control conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
65
1

Year Published

1995
1995
2009
2009

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 111 publications
(70 citation statements)
references
References 11 publications
4
65
1
Order By: Relevance
“…A wealth of evidence has accumulated for the efficacy of dietary FO in reducing CVD risk since the initial observation that Greenland Eskimos consuming a high fat diet, containing large amounts of FO, had lower death rates from CVD compared with their counterparts in Denmark [3]. Various animal models have produced similar results including pigs, monkeys, rats, dogs and mice [4][5][6][7][8][9]. Multiple mechanisms have been proposed for the cardioprotective benefits of FO including reduced blood pressure, decreased thrombosis, decreased arrhythmias, decreased inflammation, decreased endothelial activation, and decreased plasma TG concentration [10].…”
Section: Introductionmentioning
confidence: 99%
“…A wealth of evidence has accumulated for the efficacy of dietary FO in reducing CVD risk since the initial observation that Greenland Eskimos consuming a high fat diet, containing large amounts of FO, had lower death rates from CVD compared with their counterparts in Denmark [3]. Various animal models have produced similar results including pigs, monkeys, rats, dogs and mice [4][5][6][7][8][9]. Multiple mechanisms have been proposed for the cardioprotective benefits of FO including reduced blood pressure, decreased thrombosis, decreased arrhythmias, decreased inflammation, decreased endothelial activation, and decreased plasma TG concentration [10].…”
Section: Introductionmentioning
confidence: 99%
“…Biochemical research revealed that the very long-chained n-3 polyunsaturated fatty acids (n-3 VLCPUFA), abundantly present in ®sh fat, are potent modulators of human metabolism. Among numerous metabolic effects, n-3 VLCPUFA lower fasting and postprandial plasma concentrations of triglyceride-rich lipoproteins and their remnants, and they modify the eicosanoid pro®le and cardiac excitability in a way that might lead to a reduced risk of CHD (Harris, 1989;Dyerberg, 1981;Schacky et al, 1985;Nordùy et al, 1994;McLennan et al, 1993;Kang & Leaf, 1994). Potentially athero-and thrombogenic effects have also been reported.…”
Section: Introductionmentioning
confidence: 99%
“…10 Possible effects of Ͻ1 g EPA and DHA on platelet aggregation, endothelial function, heart rate variability, and inflammatory markers are poorly understood. Original observations in experimental myocardial infarction 11 and later studies by McLennan et al [12][13][14] in rats and monkeys suggested that omega-3 FAs had a direct protective effect on the heart itself. In a dog model of ventricular tachyarrhythmia, 15 infused omega-3 FAs reduced the number of potentially fatal arrhythmias.…”
mentioning
confidence: 98%